Institutional Environment, Entrepreneurial Self-Efficacy and Entrepreneurial Intention of Company Employees (International Journal of Applied Research in Management and Economics, 2020)
From the intentionality-based view, individuals' actual behaviors to initiate a new venture is driven by their entrepreneurial intentions. Company employees have accumulated professionalism and practical experience, which both enable them to discover some unmet market demand and industrial gaps. However, in establishing a new business, not everyone with certain knowledge or expertise has the desire to become an entrepreneur. Prior research has shown that entrepreneurial intentions are under the profound influences of intrinsic factors and extrinsic factors. On the one hand, entrepreneurial self-efficacy is one of the key psychological states that makes someone dare to initiate entrepreneurial activities. Institutional environment, on the other hand, can either enhance and hinder an individuals' entrepreneurial motivation by offering incentives or causing barriers. Little work has been done to understand how the institutional environment and entrepreneurial self-efficacy jointly affect company employees' intention to quit their job and start an enterprising career. By using hierarchical regression on a sample of 325 Indonesian company employees, this paper shows that the entrepreneurial cognition and entrepreneurial self-efficacy are positively related to employees' entrepreneurial intentions. Also, entrepreneurial self-efficacy strengthens the effect of normative Approval on entrepreneurial intention, whereas the regulatory Support from Government is detrimental to company employees' intention to start a new venture regardless the entrepreneurial self-efficacy is high or low.